Persistent Core Populations Shape the Microbiome Throughout the Water Column in the North Pacific Subtropical Gyre - Mende, Daniel R.; Boeuf, Dominique; DeLong, Edward F. (Frontiers in Microbiology, 2019)
Marine microbial communities are responsible for many important ecosystem processes in the oceans. Their variability across time and depths is well recognized, but mostly at a coarse-grained taxonomic resolution. To gain a deeper perspective on ecological patterns of bacterioplankton diversity in the North Pacific Subtropical Gyre, we characterized their communities throughout the water column at a fine-grained taxon level with a focus on temporally persistent core populations. Considerable intra-clade microdiversity was evident in virtually every planktonic microbial group examined. A smaller number of the most abundant populations formed a temporally persistent core, that were found within a much more diverse array of lower abundance ephemeral clade variants. Within-clade subclusters from diverse phylogenetic groups reflected the discrete depth distributions of their corresponding members, indicating that depth-stratified, ecotypic variation was the rule among most oligotrophic planktonic bacterial and archaeal clades. Our results suggested that the abundant, persistent core populations comprised the bulk of the biomass within any given clade. As such, we postulate that these core populations are largely responsible for microbially-driven ecosystem processes, and so represent ideal targets for elucidating key microbial processes in the open-ocean water column.